Measurement of the differential inclusive B+ hadron cross sections in pp collisions at root s=13TeV - KAYA, MİTHAT (ELSEVIER, 2017)
The differential cross sections for inclusive production of B+ hadrons are measured as a function of the B+ transverse momentum p(T)(B) and rapidity y(B) in pp collisions at a centre-of-mass energy of 13 TeV, using data collected by the CMS experiment that correspond to an integrated luminosity of 48.1 pb(-1). The measurement uses the exclusive decay channel B+ -> J/psi K+, with J/psi mesons that decay to a pair of muons. The results show a reasonable agreement with theoretical calculations within the uncertainties. (C) 2017 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Physics; B-physics; P(P)OVER-BAR COLLISIONS; D-SIGMA/DP(T); MESON